Hubungan Sarana Sanitasi Dengan Tingkat Kepuasan Pengunjung Di Terminal Penumpang Pelabuhan Penyeberangan Kariangau Balikpapan - Hidayat, Hidayat; Inayah, Inayah; Rachman, Erwinda Alwi; Arana, Yurika Dwi Nanda (Sulolipu: Media Komunikasi Sivitas Akademika dan Masyarakat, 2025)
Harbor is a public place that is used as where the ship docks, boarding passengers and loading and unloading goods in the form of terminals and berths of ships and can act as door of exit and entry of various kinds of infectious diseases including quarantine disease This study aims to determine the relationship of means sanitation with the level of visitor satisfaction at the passenger terminal Kariangau Harbor, Balikpapan. Total population of 198 and total sample of 132 samples. This research method is research analytic observational with a cross sectional approach to the method sampling using purposive sampling and data analysis do statistical tests.The results of this study indicate that there is a relationship between water supply with visitor satisfaction with p-value = 0.002<0.05, toilet with visitor satisfaction with p-value= 0.003 <0.05, trash can with visitor satisfaction with p- value = 0.041 <0.05, sewerage with satisfaction visitor with p-value=0.000<0.05, existence vector with visitor satisfaction with p-value=0.000<0.05. And nothing relationship between handwashing places and visitor satisfaction with p-value = 0.235> 0.05, where food sellers are satisfied visitors with p-value=0.080>0.05. The conclusion is that there is a relationship between the provision of clean water, toilets, trash cans, sewers, presence of vectors with visitor satisfaction and there is no relationship between washing places hands and food vendors with visitor satisfaction. Improving the quality of sanitation facilities and providing sanitation facilities additions in order to provide the comfort of visitors while in port area